Treatment-seeking behavior among people affected by neglected tropical diseases in Koshi Province, Nepal - Thapa, Janak K.; Dahal, Harsha R.; Thapa, Salina; Nepal, Chiranjibi; Baral, Bhuwan; Balampki, Pabitra; Pokharel, Pragya; Luitel, Sushant; Thapa, Deependra K. (International Journal Of Community Medicine And Public Health, 2025)
Background: Understanding the treatment-seeking behavior of individuals affected by Neglected Tropical Diseases (NTDs) is crucial for improving access to care and controlling disease spread. Identifying care-seeking barriers and facilitators enables targeted health interventions and policies for NTD-affected populations. The aim is to assess treatment-seeking behavior and associated factors among patients affected by NTD. Methods: Community-based cross-sectional study was conducted among 102 participants (leprosy 70, Lymphatic Filariasis 32) in Koshi Province of Nepal. A standardized, pre-tested questionnaire assessed treatment-seeking behaviour, and socio-demographic and disease related characteristics. Factors associated with treatment seeking bahviour were estimated using logistic regression. Results: Around two-thirds (65.7%) of the patients affected by NTDs sought treatment in the past 12 months. Around 12% of the patients who received treatment from health workers still needed to complete the prescribed medication regimen. Religion, financial support, and types of NTDs are significantly associated with treatment-seeking behavior. Conclusions: NTDs affected persons from younger age groups with informal education should be targeted to improve their treatment-seeking behaviour. Expanding health insurance schemes to include NTD may reduce the out-of-pocket expenditure on receiving treatment from the health post.